TRANSLATION PROCESS IN “SONET 12” BY WILLIAM SHAKESPEARE: TRANSLATION STUDIES - Mayasari Mayasari (BAHAS, 2018)
The paper revisits the concepts of translation process by Newmark (1988). Translation as a product is a written text in a target language as the end result of a translation process for a source-language text. Following the Newmark’s (1988) theory, the writer analyzed the text around the analysis of the source text, transfer of the text into the target language and revision of the translation.